2019
DOI: 10.1007/s10071-019-01277-y
|View full text |Cite
|
Sign up to set email alerts
|

Positional encoding in cotton-top tamarins (Saguinus oedipus)

Abstract: Strategies used in artificial grammar learning can shed light into the abilities of different species to extract regularities from the environment. In the A ( X ) n B rule, A and B items are linked, but assigned to different positional categories and separated by distractor items. Open questions are how widespread is the ability to extract positional regularities from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Gómez found that in some conditions (see below) adults and infants are able to learn these nonadjacent dependencies, discriminating between sequences which conform to or violate the dependency. This result has been confirmed in further experiments involving adults (e.g., Frost & Monaghan, 2016; Gómez, 2002; Pena, Bonatti, Nespor, & Mehler, 2002; van den Bos, Christiansen, & Misyak, 2012; Vuong, Meyer, & Christiansen, 2016) and infants (e.g., Gómez, 2002; Gómez & Maye, 2005) as well as nonhuman animals (e.g., Milne et al., 2016; Newport et al., 2004; Ravignani, Sonnweber, Stobbe, & Fitch, 2013; Sonnweber, Ravignani, & Fitch, 2015; Versace, Rogge, Shelton‐May, & Ravignani, 2017), although successful learning only occurs under certain conditions (see Section 3, below).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Gómez found that in some conditions (see below) adults and infants are able to learn these nonadjacent dependencies, discriminating between sequences which conform to or violate the dependency. This result has been confirmed in further experiments involving adults (e.g., Frost & Monaghan, 2016; Gómez, 2002; Pena, Bonatti, Nespor, & Mehler, 2002; van den Bos, Christiansen, & Misyak, 2012; Vuong, Meyer, & Christiansen, 2016) and infants (e.g., Gómez, 2002; Gómez & Maye, 2005) as well as nonhuman animals (e.g., Milne et al., 2016; Newport et al., 2004; Ravignani, Sonnweber, Stobbe, & Fitch, 2013; Sonnweber, Ravignani, & Fitch, 2015; Versace, Rogge, Shelton‐May, & Ravignani, 2017), although successful learning only occurs under certain conditions (see Section 3, below).…”
Section: Introductionmentioning
confidence: 63%
“…By contrast, tamarins were able to learn the dependencies based on syllables and vowels, but not consonants, suggesting that the vowel sounds (including within syllables) might be particularly salient to the monkeys (Newport et al., 2004). Recently, nonadjacent dependency learning has been demonstrated in the visual modality in tamarins (Versace et al., 2017) and baboons (Malassis, Rey, & Fagot, 2018), suggesting that these abilities are not limited to the auditory domain. de la Mora and Toro (2013) presented rats with sequences of nonsense words of alternating consonants and vowels of the form “CVCVCV,” containing nonadjacent dependencies between either the vowels or the consonants.…”
Section: Nonadjacent Dependency Learning In Adults Infants and Nonhmentioning
confidence: 99%
“…For example, a number of paradigms used passive learning of grammars [e.g., cotton-top tamarins, Saguinus oedipus ( 8 , 24 ); squirrel monkeys, Saimiri sciureus ( 5 )], while others actively trained subjects via operant conditioning [e.g., starlings, Sturnus vulgaris ( 35 ); rhesus macaques, Macaca mulatta ( 9 )]. In addition, some studies investigated sequence processing in the visual [e.g., chimpanzees ( 15 , 16 ); rats, Rattus norvegicus ( 36 ); cotton-top tamarins ( 12 )] rather than auditory domain [e.g., Bengalese finches, Lonchura striata domestica ( 14 )], and certain studies constructed their grammars from artificial stimuli [e.g., squirrel monkeys and common marmosets ( 5 , 6 )] as opposed to using vocalizations from the study species’ own repertoire [e.g., starlings ( 13 , 35 )]. While experimental design must account for the pertinent cognitive, behavioral, and morphological profiles of a study species, it is advantageous to keep all other factors as similar as possible when aiming to facilitate fair comparisons across species ( 19 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the majority of studies have found that, multiple species of animals are able to process regular grammars, specifically, (AB) n sequences (ravens, Corvus corax, Reber et al 2016; kea, Nestor notabilis, and pigeons, Columba livia, Stobbe et al 2012; cf. ten Cate and Okanoya 2012) and perceptual dependencies between edge stimuli in AB n A sequences both in the visual domain (chimpanzees, Pan troglodytes, Sonnweber et al 2015; cotton-top tamarins, Saguinus oedipus, Versace et al 2019) and in the auditory domain (squirrel monkeys, Saimiri sciureus, Ravignani et al 2013; cotton-top tamarins, Saguinus oedipus, Newport et al 2004; common marmosets, Callithrix jacchus, Reber et al 2019). In addition, although some research has suggested that birds are able to process supra-regular grammars (Abe and Watanabe 2011;Gentner et al 2006), subsequent studies have shown that these birds might have used simple strategies-that do not require any of the computational power at the level of supra-regular automata-to parse these structures (Ravignani et al 2015;Van Heijningen et al 2009).…”
Section: The Animal Ability To Process Compositional Rules In Vocal Umentioning
confidence: 99%